Low serum levels of meteorin-like/subfatin: an indicator of diabetes mellitus and insulin resistance? - Onalan, Erhan; Cavli, Cundullah; Dogan, Yusuf; Onalan, Ebru; Gozel, Nevzat; Buran, Ilay; Donder, Emir (Via Medica, 2020)
Introduction: Meteorin-like (Metrnl), also known as subfatin, is a recently discovered adipokine with a favourable effect on insulin sensitivity. Studies have shown lower Metrnl levels in obese patients. However, data on its circulating levels in type 2 diabetes mellitus (T2DM) patients are contradictory. This study aims to evaluate serum Metrnl levels in T2DM patients and determine the relationship between serum Metrnl levels and insulin resistance in these patients. Material and methods: This cross-sectional study was conducted among 150 participants. The study was carried out between June 2019 and December 2019 at the internal medicine outpatient clinic of a tertiary university hospital. The participants were divided into three groups: group 1 (control group, n = 50), group 2 (newly diagnosed T2DM, n = 50), and group 3 (long-standing diagnosed T2DM, n = 50). An enzyme-linked immunosorbent assay (ELISA) was used to measure the serum levels of Subfatin (Metrnl), and the correlations of Metrnl level with anthropometric parameters, HOMA index, and biochemical measurements were assessed. Results: There was no statistically significant difference between the gender (p = 0.468) and age (p = 0.067) characteristics of the three groups. The Metrnl (subfatin) levels of the participants were as follows: control group -20.05 (1.56-103.78); newly diagnosed T2DM group - 2.62 (1.25-103.78); and long-standing diagnosed T2DM group - 2.01(0.80-19.84) pg/mL. The Metrnl (subfatin) levels of the participants in the control group were higher than in the participants in the newly diagnosed T2DM and long-standing diagnosed T2DM groups (p < 0.001). Subfatin demonstrated a negative correlation with insulin and HOMA-IR in the control group and long-standing diagnosed T2DM group. Conclusions: The subfatin level was found to be higher in the healthy control group than in both diabetic patient groups. Subfatin level showed negative correlation with both insulin level and HOMA index. There was a relationship between subfatin and insulin resistance. Low levels of subfatin in the diabetic patient groups may play a role in the pathogenesis of T2DM by increasing insulin resistance.
Keywords: subfatin/meteorin-like; type 2 diabetes mellitus; insulin resistance; newly diagnosed T2DM